CP-136 Inappropriate prescribing in older patients:assessment of a screening tool based on the stopp and start criteria. (24th March 2015) - Sennesael, AL; Dalleur, O; Artoisenet, C; Hecq, JD; Schoevaerdts, D; Spinewine, A
Abstract : Background: Inappropriate prescribing is a problem of major concern in older patients, given the increased risk of adverse drug events and mortality. In this context, a 24-item tool based on the Screening Tool for Older Person's Prescriptions (STOPP) and Screening Tool to Alert doctors to Right Treatment (START) criteria 1 was developed and applied in the geriatric unit. Purpose: To find out whether the implementation of this screening tool led to a reduction in potentially inappropriate medicines (PIMs) and potential prescribing omissions (PPOs) during the hospitalisation. Material and methods: We conducted a retrospective interrupted time series analysis. Four periods were selected between February and September 2013: (1) baseline evaluation; (2) the tool was made available in the unit; (3) three months later; and (4) a clinical pharmacist held weekly meetings with interns to review treatments using the tool, which was incorporated in the electronic medical record. Data were collected from the discharge letter. The primary outcome was the rate of PIMs discontinued and PPOs corrected during hospitalisation. Results: 120 patients (median age 85 years) were included. The prevalence of PIMs and PPOs on admission were 56% and 51% respectively. At baseline (period 1), one fifth of PIMs were discontinued during hospitalisation while 22% of PPOs were corrected. The reduction in PIMs and amendment of PPOs increased when the screening tool was made available in the unit (period 2; 26% and 38% respectively), but three months later this effect had disappeared (period 3; 15% and 19% respectively). We observed the greatest reduction in PIMs and PPOs for the last study period (period 4; 58% and 43% respectively). Conclusion: The use of a screening tool contributes to improving appropriateness of prescribing in older patients. A multidisciplinary approach provides the greatest reduction in PIMs and PPOs. References and/or Acknowledgements: 1 Gallagher P, Ryan C, Byrne S, et al . STOPP (Screening Tool of Older Person's Prescriptions) and START (Screening Tool to Alert doctors to Right Treatment). Consensus validation. Int J Clin Pharmacol Ther 2008;46:72–83 No conflict of interest.